Critical Review—Identifying Critical Gaps for Polymer Electrolyte Water Electrolysis Development. Issue 4 (25th February 2017) - Babic, Ugljesa; Suermann, Michel; Büchi, Felix N.; Gubler, Lorenz; Schmidt, Thomas J.
Abstract : Although polymer electrolyte water electrolyzers (PEWEs) have been used in small-scale (kW to tens of kW range) applications for several decades, PEWE technology for hydrogen production in energy applications (power-to-gas, power-to-fuel, etc.) requires significant improvements in the technology to address the challenges associated with cost, performance and durability. Systems with power of hundreds of kW or even MWs, corresponding to hydrogen production rates of around 10 to 20 kg/h, have started to appear in the past 5 years. The thin (∼0.2 mm) polymer electrolyte in the PEWE with low ohmic resistance, compared to the alkaline cell with liquid electrolyte, allows operation at high current densities of 1–3 A/cm 2 and high differential pressure. This article, after an introductory overview of the operating principles of PEWE and state-of-the-art, discusses the state of understanding of key phenomena determining and limiting performance, durability, and commercial readiness, identifies important 'gaps' in understanding and essential development needs to bring PEWE science & engineering forward to prosper in the energy market as one of its future backbone technologies. For this to be successful, science, engineering, and process development as well as business and market development need to go hand in hand.